2020
DOI: 10.1002/star.201900285
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Structural and Physicochemical Properties of Corn Flour after Fermentation with Lactobacillus plantarum Y1

Abstract: Corn flour is fermented with Lactobacillus plantarum Y1 at 37°C for 60 h to modify its functional properties. The effects of the fermentation on structural and physicochemical properties of corn flour, starch, zein, and glutelin are investigated. Swelling power, solubility, water binding capacity, and light transmittance of corn flour increases significantly after fermentation. The fermentation process reduces the hardness and retrogradation tendency of corn flour dough; while, viscidity, elasticity, and cohes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It contains about 62% of starch, 8.7% of protein, and 4% of fat and is full of potassium, phosphorus, iron, zinc, calcium, vitamin A, vitamin B5, vitamin B6, and carotene pigment. Another health benefit of corn is that it also contains bioactive compounds such as lutein and zeaxanthin (Hassan et al ., 2019; Qi et al ., 2020). In Central American countries, products made from corn flour are regarded as essential food staples, such as corn tortillas and their sub‐products, which are excellent pasta products to improve the nutritional health of the population (Escalante‐Aburto et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It contains about 62% of starch, 8.7% of protein, and 4% of fat and is full of potassium, phosphorus, iron, zinc, calcium, vitamin A, vitamin B5, vitamin B6, and carotene pigment. Another health benefit of corn is that it also contains bioactive compounds such as lutein and zeaxanthin (Hassan et al ., 2019; Qi et al ., 2020). In Central American countries, products made from corn flour are regarded as essential food staples, such as corn tortillas and their sub‐products, which are excellent pasta products to improve the nutritional health of the population (Escalante‐Aburto et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The close interactions of starch, protein, and fat in maize limit the water absorption and expansion of corn flour, leading to poor quality in processing. Hence, corn and corn flour are mainly used as a feed or industrial raw materials, resulting in a huge waste of food resources ( 4 ). Studies have shown that around 78% of corns in developed countries are used in the feed industry, whereas only around 5% of corns are directly consumed.…”
Section: Introductionmentioning
confidence: 99%